A visão do usuário sobre o serviço público odontológico e a autopercepção em saúde bucal - Ayach, Carlos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The user's opinion in assessing the quality of health services is an important tool in public management. The aim of this study was to analyze the users' satisfaction with dental services in the Public Health System and self-perception of oral health status. This is a survey-type cross-sectional study, part of a multicenter study conducted in three municipalities in Brazil. Data collection was in the city of Aquidauana, MS, in 2013, given to the calculation of the total sample of the adult population in the study area, with a prevalence of 50% satisfied with the services provided. We interviewed 390 users in dental treatment in primary care from the public network, using an adapted form of the instruments of the Ministry of Health, proposed for the National Program of Health Services Evaluation (PNASS) and Access Improvement Programme and quality (PMAQ). The exclusion criteria were considered users who would hold the first consultation, to submit any failure to respond to the instrument, and children under 18 years.From the total respondents, 73% were women; 47.2% aged 20-39 years; 56.4% were in dental treatment; 26.9% sought pain of reason. As to the satisfaction of the service provided in relation to access, 97.7% were satisfied with the way they were received in the health unity; 75.1% said that there was no delay in appointing the first visit; 94.1% were satisfied with the scheduling time; 79% said that consultation was marked by order of arrival; 77.2% considered that the distance from home to the office was short; 24% were referred to specialized service and of these, 88% were scheduled, and 66.7% were satisfied to have scheduled in the specialized service. Regarding humanization, 55.6% said that the care given by the oral health team was very good; 96.4% were satisfied with the service provided; whereas 96.9% considered...

A opinião do usuário na avaliação da qualidade dos serviços de saúde constitui-se em uma importante ferramenta na gestão pública. Nesta pesquisa, objetivou-se analisar a satisfação dos usuários com o serviço odontológico no Sistema Único de Saúde e a autopercepção da saúde bucal. Trata-se de um estudo transversal, tipo inquérito, parte de um projeto multicêntrico realizado em três municípios do Brasil. A coleta de dados foi no município de Aquidauana, MS, no ano de 2013, considerando-se para o cálculo da amostra o total da população adulta na região estudada, com prevalência de 50% de satisfeitos com os serviços prestados. Foram entrevistados 390 usuários, em tratamento odontológico na atenção básica da rede pública, empregando-se um formulário adaptado dos instrumentos do Ministério da Saúde, propostos para o Programa Nacional de Avaliação de Serviços de Saúde (PNASS) e pelo Programa de Melhoria do Acesso e Qualidade (PMAQ). Como critério de exclusão, foram considerados usuários que iriam realizar a primeira consulta, os que apresentassem alguma impossibilidade de responder ao instrumento utilizado e os menores de 18 anos. Do total de entrevistados, 73% eram mulheres; 47,2% tinham de 20 a 39 anos; 56,4% estavam em tratamento odontológico; 26,9% procuraram por motivo de dor; 24% já tinham sido referenciados para o serviço odontológico especializado e a maioria dos encaminhados conseguiu agendar o tratamento. Quanto à satisfação com o serviço oferecido, em relação ao acesso, 97,7% estavam satisfeitos com a forma com que foram recebidos na Unidade; 75,1% disseram que não houve demora na marcação da primeira consulta; 94,1% estavam satisfeitos com o tempo de agendamento; 79% afirmaram que a consulta foi marcada por ordem de chegada; 77,2% consideraram próxima...
Keywords: Sistema Único de Saúde (Brasil); Percepção; Saúde bucal; Oral Health